If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 6 + -3 = -5 Reorder the terms: 6 + -3 + 8b = -5 Combine like terms: 6 + -3 = 3 3 + 8b = -5 Solving 3 + 8b = -5 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8b = -5 + -3 Combine like terms: 3 + -3 = 0 0 + 8b = -5 + -3 8b = -5 + -3 Combine like terms: -5 + -3 = -8 8b = -8 Divide each side by '8'. b = -1 Simplifying b = -1
| 14=-8x+x | | 7x^2+68x+25=0 | | 3c+-2=-2-9c | | r/-3=2 | | -7k+21= | | x+28=3x+45 | | 4x+.33=.5x+5.5 | | 45=4x+7 | | 3(x-5)+18=2(2+4) | | 8x^3+50x=0 | | 3a^2-10a-125=0 | | 3+9n-2=2n+4-3n | | (125x-108)/(14x-15)=8 | | K=2/3tc | | 2/3x-4/3 | | (125x-108)/(14x-15)8 | | 6x-4+8x=-4 | | (125*x-108)/(14*x-15) | | .25/.5=m/8 | | (4+i)-(2+3i)=0 | | 5x^2*6x^2= | | x-38=18-6x | | x+60*0+1=1 | | 9x+4(x+9)= | | 2/3•t=9 | | x+60*0+1=11 | | -2b-6+b-2= | | 2xy*x= | | x+60*0+1=61 | | 60+60*0+x=61 | | X=(2-3k)y | | 17/50=x/25 |